Índice de prevalencia de micoplasmosis en pollos de engorde en granjas de los sectores de mayor producción de la provincia de El Oro - Ordóñez Sarango, Adrián Enrique (2015)
The poultry industry in our province has a high incidence productive since it goes from the production of maize for the formulation of balanced food, breeding, production, industrialization and commercialization of chicken and eggs. In the commercial poultry management and health are very important for the production. Diseases of the appliances respiratory and digestive are very important for the conditions of intensive management causing alterations in the microflora of the birds by stress. In the respiratory system the presence of mycoplasmosis represents a high economic impact due to the discards, morbidity and mortality. The presence of problems productive in the upper area of the province of El Oro, we were motivated to perform a task of primodiagnostico of Mycoplasmosis in broilers in farms of these sectors. The work was carried out in canton of Piñas, Balsas and Marcabelí, in stocks poultry of different driving conditions. The work began taking blood samples in farms: eight in Piñas, nine in Balsas and six in Marcabelí. Agglutination Test Quickly on board, proceeded to the blood sample, place it on a glass plate, without compounding the antigen for MG and MS respectively and are appropriate to your analysis. The total number of samples analyzed was 605 whose results were: in Piñas for MG, (69.47 %) were positive, (30.53 %) negative and for MS (77.54 %) were positive and (22.47 %) negative. For the canton Balsas for MG (65.5 %) and positive (34.5 %) negative and for MS (68.50 %) were positive and a (31.5 %) negative; in the canton Marcabelí tests for MG (80 %) were positive (20 %) negative while for MS the results were (91.7 %) were positive and (8.3 %) negative. These results show that the incidence of mycoplasms is extremely high and the productions are affected by this reason.